PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E DAPAT MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 34 PADANG - Santiva, Orin Oriza (Jurnal Edukasi dan Penelitian Matematika, 2023)
Abstract — Understanding concept is a basic ability thati needs to be mastered by students. However in reality, this level of understanding for class VIII students of SMP Negeri 34 Padang is still low. The solustion is to apply learning cycle 7e learning models. The purpose of this study is to show that the understanding of the concept of learners who use the learning cycle 7e learning model is better than the conventional learning model. The type of research used was a quasy experiment whit the non-equivalent posttest-only control group design. The population is students of class VIII SMP Negeri 34 Padang, class VIII.6 and VIII.7 as the sample class. The instrument used was the final test of concept understanding. After the t-test was conducted, the P-value  means that H0 is rejected. So it is concluded that the understanding of the concept of students who use the learning cycle 7e learning model is beter than those using the conventional learning model. In the other words, the application of learning cycle 7e model can improve concept understanding students class VIII SMPN 34 Padang.Keywords —Learning Cycle 7E, Understanding of Mathematical Concept, Conventional  Learning